Promosi Kesehatan Jiwa Masyarakat Dengan Pendekatan Komunikasi Interpersonal: Literatur Review - Lina Eta Safitri; Jamaluddin Jamaluddin; Putri Salsawina Chalista; Zamsinar Kurnia Putri; Irvan Hunggurami; Heri Hunggurami (Pusat Riset dan Inovasi Nasional, 2024)
Mental health in Indonesia has so far been relatively neglected, even though the decline in productivity due to mental health disorders has been proven to have a real impact on the economy. Interpersonal communication is a scientific discipline that is seen as capable of realizing a person's mental health, because within the scope of its study, interpersonal communication is dialogical in nature. The dialogic nature is demonstrated through verbal communication in conversations that display direct feedback. This study uses all articles presented in the form of a literature review regarding